Manual of pediatric balance disorders - O'Reilly, Robert; O'Reilly, Robert; Morlet, Thierry; Brodsky, Jacob R.; Cushing, Sharon L. (San Diego c)
"This thoroughly updated second edition of Manual of Pediatric Balance Disorders remains a vital resource for clinicians and students specializing in pediatric vestibular and balance disorders. The text is organized for effective use in the clinic, classroom, bedside, or laboratory, and is separated into four parts: Basic Mechanisms, Clinical Evaluation, Pediatric Vestibular Disorders, and Treatment. Each chapter ends with Self-Assessment Questions to aid in reader comprehension and address important chapter topics. Manual of Pediatric Balance Disorders features contributions from 45 experts across the fields of otolaryngology, audiology, neurology, and physical therapy, and represents the distillation of years of cumulative clinical and research experience"--
Keywords: Audiology